A Comparative Analysis of Recombinant Human Bone Morphogenetic Protein-2 with a Demineralized Bone Matrix versus Iliac Crest Bone Graft for Secondary Alveolar Bone Grafts in Patients with Cleft Lip and Palate: Review of 501 Cases. Issue 2 (August 2017) - Hammoudeh, Jeffrey A.; Fahradyan, Artur; Gould, Daniel J.; Liang, Fan; Imahiyerobo, Thomas; Urbinelli, Leo; Nguyen, JoAnna T.; Magee, William; Yen, Stephen; Urata, Mark M.
Abstract : Background: Alveolar cleft reconstruction using iliac crest bone graft is considered standard of care for children with complete cleft lip and palate at the time of mixed dentition. Harvesting bone may result in donor-site morbidity and additional operating time and length of hospitalization. Recombinant human bone morphogenetic protein (rhBMP)-2 with a demineralized bone matrix is an alternative bone source for alveolar cleft reconstruction. The authors investigated the outcomes of rhBMP-2/demineralized bone matrix versus iliac crest bone graft for alveolar cleft reconstruction by reviewing postoperative surgical complications and cleft closure. Methods: A retrospective chart review was conducted for 258 rhBMP-2/demineralized bone matrix procedures (mean follow-up, 2.9 years) and 243 iliac crest bone graft procedures (mean follow-up, 4.1 years) on 414 patients over a 12-year period. The authors compared complications, canine eruption, and alveolar cleft closure between the two groups. Results: In the rhBMP-2/demineralized bone matrix group, one patient required prolonged intubation because of intraoperative airway swelling not thought to be caused by rhBMP-2, 36 reported facial swelling and one required outpatient steroids as treatment, and 12 had dehiscence; however, half of these complications resolved without intervention. Twenty-three of the 228 rhBMP-2/demineralized bone matrix patients and 28 of the 242 iliac crest bone graft patients required repeated surgery for alveolar cleft repair. Findings for canine tooth eruption into the cleft site through the graft were similar between the groups. Conclusions: The rhBMP-2/demineralized bone matrix appears to be an acceptable alternative for alveolar cleft repair. The authors found no increase in serious adverse events with the use of this material. Local complications, such as swelling and minor wound dehiscence, predominantly improved without intervention. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.